ChatGPT and Legal Education in Indonesia: Examining Readiness and Implications - Al Asyari, Haekal; Halim, Hanif Abdul; Roselynn Nikita Tan, Rachelle Amadea (Journal of Indonesian Legal Studies, 2025)
ChatGPT has demonstrated significant development and found practical applications in legal education. Due to its usability, accessibility, and rapid development, ChatGPT is expected to enhance students' and lecturers’ experience, improve legal research, personalize learning, and offer real-time feedback and support to students. Some countries have even imposed restrictions on the use of ChatGPT. In Indonesia, ChatGPT has gained significant traction, making it crucial to examine its implications for legal education. This empirical study found that despite optimistic projections in scholarly literature, Indonesian law schools remain skeptical about ChatGPT’s role in legal studies and teaching. In terms of readiness, while ChatGPT is actively used in legal research, case and law analysis, legal writing, and examinations, its integration into legal education lacks institutional policies, curriculum adjustments, and sufficient digital literacy programs. While lecturers have experimented with AI more frequently, students are its primary users. The implications of ChatGPT’s use include concerns over plagiarism, academic integrity, and its potential to hinder critical thinking, alongside its limitations in handling complex legal reasoning. However, ChatGPT has already reshaped legal education, influencing students’ approaches to legal research, writing, and assessments, as well as lecturers’ methods of preparing teaching materials and evaluations. These findings highlight the need for law schools to establish AI governance frameworks, modify assessment methods, and enhance digital literacy to ensure ChatGPT’s responsible and effective integration into legal education.